The Moderating Effect of Debt to Asset Ratio (DAR) to Audit Delay - Souisa, Stefany Aurelia; Satria, Indra; Sudarmaji, Eka (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2023)
This research aims to determine the ability of the debt to asset ratio (DAR) in moderating the factors that affect audit delay. By using a purposive sampling technique, the samples in this study were 27 food and beverage companies listed on the IDX for the 2019-2021 period. Multiple regression analysis and Moderated Regression Analysis were the analytical tools used in this study. The results of this study prove that the gross profit margin has an influence on audit delay, audit complexity and an independent board of commissioners have no effect on audit delay. DAR is able to moderate the effect of gross profit margin on audit delay and DAR is able to moderate the effect of gross profit margin on audit delay, while DAR is unable to moderate between independent commissioners on audit delay. DAR strengthens the effect of the independent variable on the dependent variable as evidenced by the Adjusted R² value before the moderating variable was 12.5% after adding the moderating variable to 30.2%. The results of this study can help company management to estimate audit time and identify factors that need attention in order to reduce audit delay and become the basis for regulators to increase supervision of companies that have factors that can affect audit delay.